The Influence of Digital Literacy on the Work Readiness of Final-Year Students at Padang State University - Zalfa Jihan Aqillah; Suci Rahma Nio (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although digital literacy has received increasing attention in graduate employability research, evidence regarding its contribution to work readiness among final-year students across multiple study programs within a single Indonesian public university remains limited. This study aimed to examine the influence of digital literacy on the work readiness of final-year students at Padang State University. A quantitative approach with a simple regression design was employed, involving 335 final-year students from nine faculties selected through purposive sampling. Data were collected using a Digital Literacy Scale adapted from Nafiah (2023) and a Work Readiness Scale adapted from Afaf (2022) and analyzed through simple linear regression using IBM SPSS Statistics 27. The results revealed that digital literacy had a positive and statistically significant influence on work readiness, as represented by the regression equation Y = 106.614 + 0.279X. The coefficient of determination (R² = 0.645) indicated that digital literacy accounted for 64.5% of the variance in students’ work readiness. These findings demonstrate that digital literacy is an important factor in strengthening final-year students’ readiness to enter the workforce and contribute to the literature on digital competence and career preparation within educational and organizational psychology. The study underscores the importance of integrating digital competencies into university curricula and career-preparation programs to facilitate students’ transition from higher education to the labor market.